2017
DOI: 10.1513/annalsats.201612-1023oc
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Incidental Findings and Subsequent Evaluation in Low-Dose Computed Tomographic Scans for Lung Cancer Screening

Abstract: Clinically significant IFs on LDCT scans for lung cancer screening are common, and their potential impact should be included in the shared decision-making process. Screening program staff should develop a standard approach for the evaluation of these findings and consider the financial impact when seeking infrastructure support for screening program implementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
90
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(90 citation statements)
references
References 25 publications
0
90
0
Order By: Relevance
“…Second, guideline-based interventional pulmonology review effectively reduced false positives and unnecessary invasive testing. Prior screening and incidental nodule studies have reported false positive rates as high as 96% [9,24]. In our program, guideline-based interventional pulmonology review in Year 1 eliminated 1,127 of the original 1,792 CT scans identified by the radiology search to yield 665 nodules requiring intervention or radiologic follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Second, guideline-based interventional pulmonology review effectively reduced false positives and unnecessary invasive testing. Prior screening and incidental nodule studies have reported false positive rates as high as 96% [9,24]. In our program, guideline-based interventional pulmonology review in Year 1 eliminated 1,127 of the original 1,792 CT scans identified by the radiology search to yield 665 nodules requiring intervention or radiologic follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The cohort eligible for LDCT screening, based on smoking history and age, has been shown to frequently have comorbidities (eg, hypertension in about 60%, hyperlipidemia in approximately 50%, COPD in about 30%, coronary artery disease in 15%, diabetes mellitus in 15%). 141 As such, it is not surprising that many LDCT screening scans reveal incidental findings (other than pulmonary nodules). 50,74,75,[141][142][143] The value of what amounts to screening for other findings is undefined; the balance of benefits and harms of lung cancer screening is affected if a significant portion of those screened undergo investigation of incidental findings.…”
Section: Structured Radiology Reportingmentioning
confidence: 99%
“…141 As such, it is not surprising that many LDCT screening scans reveal incidental findings (other than pulmonary nodules). 50,74,75,[141][142][143] The value of what amounts to screening for other findings is undefined; the balance of benefits and harms of lung cancer screening is affected if a significant portion of those screened undergo investigation of incidental findings. Therefore, management of incidental findings is an important part of implementation of a screening program.…”
Section: Structured Radiology Reportingmentioning
confidence: 99%
“…In addition to identifying nodular lesions suspected of being LC, CT offers the benefit of incidental findings of other diseases, such as benign lung diseases (COPD, interstitial diseases, and bronchiectasis) and cardiovascular diseases (based on the degree of coronary artery calcification), at earlier stages; such findings are present in 24% to 64% of cases. (27) However, LC screening is not yet available in Brazil via the Brazilian Unified Health Care System. Brazilian National Ministry of Health Directive no.…”
Section: Discussionmentioning
confidence: 99%